ANALYSIS OF WORKLOAD AND COMPETENCY ON EFFECTIVENESS EMPLOYEES WITH TRAINING AS A MODERATING VARIABLE AT PT PLN (PERSERO) UID NORTH SUMATRA - Emmy Robiyah; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of workload and competence on employee effectiveness with training as a moderating variable at PT PLN (Persero) UID North Sumatra. This quantitative study was conducted with the aim of adjusting the research and analyzing the effect of workload and competence on employee effectiveness, with training as a moderating variable at PT PLN (Persero) UID North Sumatra. Data were collected from 81 customer service unit employees. The results of the study indicate that workload has a negative and significant effect on employee effectiveness, competence and training have a positive and significant effect on employee effectiveness. Training does not act as a moderating variable between the effect of workload and competence on employee effectiveness.